Pemetaan Potensi Desa Tugu Utara sebagai Desa Wisata - Surtaryo, Surtaryo; Artiani, Gita Puspa; Rodji, Achmad Pahrul; Wahyono, Herry (Universitas Pahlawan Tuanku Tambusai, 2024)
The mapping of Tugu Utara Village’s potential as a tourism destination aims to identify and optimize the village’s assets for sustainable tourism development. Tugu Utara was chosen due to its abundant natural resources, including Telaga Saat and its water springs, and the need to address challenges in waste and sanitation management. The methodology includes field surveys, interviews with local leaders, and data analysis using Geographic Information Systems (GIS). The mapping results reveal significant tourism potential with supporting facilities such as glamping and food courts. However, improvements in waste and sanitation management are essential to ensure environmental sustainability. This mapping provides a crucial foundation for further development, indicating that Tugu Utara Village can become a prime tourism destination with proper planning and effective environmental management.